Environmental pollutants and the immune response - Suzuki, Takafumi; Hidaka, Takanori; Kumagai, Yoshito; Yamamoto, Masayuki (Nature immunology, 2020)
Environmental pollution is one of the most serious challenges to health in the modern world. Pollutants alter immune responses and can provoke immunotoxicity. In this Review, we summarize the major environmental pollutants that are attracting wide-ranging concern and the molecular basis underlying their effects on the immune system. Xenobiotic receptors, including the aryl hydrocarbon receptor (AHR), sense and respond to a subset of environmental pollutants by activating the expression of detoxification enzymes to protect the body. However, chronic activation of the AHR leads to immunotoxicity. KEAP1–NRF2 is another important system that protects the body against environmental pollutants. KEAP1 is a sensor protein that detects environmental pollutants, leading to activation of the transcription factor NRF2. NRF2 protects the body from immunotoxicity by inducing the expression of genes involved in detoxification, antioxidant and anti-inflammatory activities. Intervening in these sensor–response systems could protect the body from the devastating immunotoxicity that can be induced by environmental pollutants. Exposure to environmental pollutants can lead to immune system dysfunction with severe pathological consequences. Yamamoto and colleagues review the impact of pollutants on immune function and describe potential means to ameliorate these effects.